Pengaruh Teamwork dan Retensi terhadap Kinerja dengan Kepuasan sebagai Variabel Intervening pada CV. Laksana Karoseri - Rafiif, Benizar; Darmi Astuti, Sih; Prayitno, Agus (Jurnal Dinamika Ekonomi dan Bisnis, 2024)
The success of a company is largely determined by the company's success in managing its human resources in achieving company goals. The main objective of this research is to analyze the influence of teamwork, employee retention on employee performance with job satisfaction as an intervening variable in CV. Like Karoseri Ungaran, Central Java with a total of 227 employees. The sample in this study was 100 people, due to the focus on the preparation section. The analytical tools used in this research are the outer model and inner model with the help of Partial Least Square (PLS). PLS is a Structural equation model Equation Modeling (SEM). The results of this research show that teamwork has a significant positive effect on employee performance. Employee retention has a significant positive effect on employee performance. Teamwork has a significant positive effect on employee satisfaction. Employee retention has a significant positive effect on employee satisfaction. Job satisfaction has a significant positive effect on employee performance. Teamwork is significant and indirectly influences employee performance through job satisfaction. This means that it is proven that teamwork has an indirect influence on employee performance through employee job satisfaction